2007
DOI: 10.1530/rep-06-0388
|View full text |Cite
|
Sign up to set email alerts
|

Porcine sperm motility is regulated by serine phosphorylation of the glycogen synthase kinase-3α

Abstract: Sperm functions are critically controlled through the phosphorylation state of specific proteins. Glycogen synthase kinase-3 (GSK3) is a serine/threonine kinase with two different isoforms (a and b), the enzyme activity of which is inhibited by serine phosphorylation. Recent studies suggest that GSK3 is involved in the control of bovine sperm motility. Our aim was to investigate whether GSK3 is present in porcine spermatozoa and its role in the function of these cells. This work shows that both isoforms of GSK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 38 publications
1
77
0
1
Order By: Relevance
“…The presence of GSK3 in spermatozoa was initially reported in humans [72] where only GSK3b was detected and simultaneously in bovine sperm by Somanath et al [73] where both isoforms were identified. In boar spermatozoa, both isoforms of GSK3 were identified by our group in 2007 [74]. In response to stimuli that induce the activation of the cAMP/PKA pathway in boar sperm, GSK3a and GSK3b isoforms are clearly phosphorylated in Ser21 and Ser9, respectively [74], indicating that PKA is an upstream regulator of GSK3 in boar spermatozoa.…”
Section: Glycogen Synthase Kinasementioning
confidence: 98%
See 3 more Smart Citations
“…The presence of GSK3 in spermatozoa was initially reported in humans [72] where only GSK3b was detected and simultaneously in bovine sperm by Somanath et al [73] where both isoforms were identified. In boar spermatozoa, both isoforms of GSK3 were identified by our group in 2007 [74]. In response to stimuli that induce the activation of the cAMP/PKA pathway in boar sperm, GSK3a and GSK3b isoforms are clearly phosphorylated in Ser21 and Ser9, respectively [74], indicating that PKA is an upstream regulator of GSK3 in boar spermatozoa.…”
Section: Glycogen Synthase Kinasementioning
confidence: 98%
“…In boar spermatozoa, both isoforms of GSK3 were identified by our group in 2007 [74]. In response to stimuli that induce the activation of the cAMP/PKA pathway in boar sperm, GSK3a and GSK3b isoforms are clearly phosphorylated in Ser21 and Ser9, respectively [74], indicating that PKA is an upstream regulator of GSK3 in boar spermatozoa. Furthermore, we have shown that GSK3 phosphorylation is totally dependent on PKA activity [66] and that is also downstream of the PKC and PI3K pathways [66].…”
Section: Glycogen Synthase Kinasementioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, in germinal cells and in the bovine corpus luteum, an increase in the phosphorylation of GSK3 in response to agonists that elevate intracellular concentrations of cAMP has been demonstrated (Aparicio et al 2007, Roy et al 2009, showing the interaction of cAMP and GSK3 (Fang et al 2000). Lithium also interferes with another second messenger system, the inositol pathway causing selective reductions of PKC (Manji & Lenox 1999), which has been shown to phosphorylate and inactivate GSK3 mediating acentromeric spindle stabilization in mouse oocytes (Baluch & Capco 2008).…”
Section: Gsk3 During Bovine Embryo Developmentmentioning
confidence: 99%